Faktor-Faktor Yang Mempengaruhi Produksi Jagung Di Kabupaten Kediri - Erlin Widya Fatmawati; Mohamad Bagus Yulianto (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
This purpose of this research are to determine the characteristics of respondents from corn farmers in Janti Village, Papar District, Kediri Regency and to determine the factors that have a significant effect on corn production in Janti Village, Papar District, Kediri Regency. This study used as many as 39 respondents. The method used is multiple linear regression analysis. The results of this study stated that the corn seed variable was added by 1 percent, so maize production would also increase by 6.576 percent. For the fertilizer variable added by 1 percent, the corn production will also increase by 5,633 percent. For the pesticide variable added by 1 percent, the corn production will also increase by 0.838 percent. For the labor variable, it is added by 1 percent, the corn production will also increase by 0.120 percent